Mergers & acquisitions in the Singapore banking industry. - Chee, Yulin. (2008)
The merger wave has begun its tirade in Singapore’s Banking Industry in the last few years. Using the case study approach, our study examines the financial performance of both acquiring and acquired local banks. Results indicate that acquiring banks exhibited superior financial performances in general.